Aligning English Language Teaching with Nursing Students’ Needs in Indonesia: A Classroom-Based Need Analysis - Juliana Juliana; Rizki Dhian Nushur; Nurlayli Yanti; Gopal Prasad Pandey (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2025)
Although English is recognized as a key competency for nursing students in academic and clinical settings, English instruction in many Indonesian nursing programs remains focused on General English and does not fully address profession-specific communication needs. This study investigates the alignment between current English teaching practices and nursing students’ actual communicative requirements through a classroom-based needs analysis. Using a descriptive-quantitative design supported by classroom observations and document analysis, data were collected from 202 purposively selected nursing students at the Akademi Keperawatan Kesdam Iskandar Muda Banda Aceh (AKIMBA). Questionnaire responses were analyzed using descriptive statistics, and qualitative data were examined through content analysis. The findings reveal that English is primarily used for academic purposes (80.6%), with reading identified as the strongest skill (69.3% good) and speaking the weakest (18.3% poor). Students expressed a strong preference for interactive instruction (87% favoring group or pair work) and for lecturers to act as facilitators (67.3%). Although most students preferred General English (66.8%), a significant proportion (32.7%) indicated the need for English for Specific Purposes (ESP), supporting the relevance of a blended curriculum model. These results highlight a mismatch between current instructional practices and students’ professional communication needs. The study recommends integrating communicative, student-centered approaches and progressively combining General English with English for Nursing Purposes to better prepare students for academic success and effective clinical communication. The implications of these findings contribute to ESP curriculum development in nursing education within similar institutional contexts.